Failure prediction of magnesium alloys based on improved CDM model. (15th May 2021) - Zhang, Kai; Badreddine, Houssem; Yue, Zhenming; Hfaiedh, Naila; Saanouni, Khemais; Liu, Jianlin
Abstract: The aim of this contribution is to improve the behavior and failure prediction accuracy for magnesium alloy sheet forming simulation by using advanced fully coupled Continuum Damage Mechanics (CDM) model. Starting from known fully coupled constitutive equations at large inelastic (plastic or viscoplastic) strains, three aspects are enhanced on the CDM model developed by Saanouni (2012 ). The first one concerns the accurate description of tension-compression asymmetry in yielding and hardening of magnesium alloys induced by combined slip and twinning deformations. The second concerns introducing the stress state dependence in damage evolution to improve the fracture prediction under various loading paths. The third deals with temperature and strain rate (viscosity) effects for metal forming processes at elevated temperatures. The improved fully coupled constitutive equations were implemented into finite element code ABAQUS/Explicit via user subroutine VUMAT including the specific local integration scheme to compute the state variables at each quadrature point. Various kinds of tensile tests at different temperatures and strain rates are used to determine the material parameters, and the complete identification procedure is given in details. As validation, the improved model is applied to simulate the three-point bending and circular cup deep drawing tests, the predicted results show good agreements with the experimental observations.